HBHA-IGRA and cytotoxic mediators release assays for the diagnosis of cervical tuberculous lymphadenitis - Soumaya Bchiri; Asma Bouzekri; Rym Ouni; Rim Lahiani; Emna Romdhane; Neira Dekhil; Sonia Ben Hamouda; Helmi Mardassi; Asma Ferjani; Emanuelle Petit; Véronique Corbière; Soumaya Rammeh; et al. (Microbiology Spectrum, 2023)
ABSTRACT Cervical tuberculous lymphadenitis (CTL), the most frequent extrapulmonary form of tuberculosis, is a serious health problem in Tunisia. CTL diagnosis is challenging mainly due to the paucibacillary nature of the disease and the potential misdiagnosis as cervical non-tuberculous lymphadenitis (CNTL). Here, we evaluated the performance of heparin-binding hemagglutinin (HBHA) interferon-gamma (IFN-γ) release assay (IGRA) for the diagnosis of CTL. In addition, we evaluated granzyme B, granulysin, and perforin release assays as CTL biomarkers and assessed their potential contribution to improve HBHA-IGRA performance. Peripheral blood mononuclear cells from CTL-suspected patients were stimulated with HBHA, early secreted antigenic target 6 (ESAT-6), or purified protein derivative (PPD) for 24 h in the presence of IL-7. Cytotoxic mediators and IFN-γ release were assessed by enzyme-linked immunosorbent assay. Receiver operating characteristic curves were used to evaluate the capacity of HBHA, ESAT-6, and PPD to discriminate between CTL (n = 27) and CNTL (n = 21). After applying bivariate and multivariate analyses, IFN-γ responses to HBHA appeared to offer the best distinction between CTL and CNTL, with an area under the curve of 0.9947, associated with 95.24% and 100% sensitivity and specificity, respectively. A principal component analysis showed clear clustering of the CTL versus the CNTL groups. This clustering was mainly attributed to HBHA-induced IFN-γ, PPD-induced granzyme B, and PPD-induced IFN-γ. These results thus suggest that the HBHA-IGRA provides high diagnostic accuracy for CTL versus CNTL, with high sensitivity and specificity. Combining HBHA-induced IFN-γ and PPD-induced granzyme B improves the accuracy to identify CTL. IMPORTANCE Cervical tuberculous lymphadenitis (CTL), the most frequent extrapulmonary form of tuberculosis, is currently a major health problem in Tunisia and in several regions around the world. CTL diagnosis is challenging mainly due to the paucibacillary nature of the disease and the potential misdiagnosis as cervical non-tuberculous lymphadenitis. This study demonstrates the added value of the heparin-binding hemagglutinin-interferon-gamma release assay as an immunoassay in the context of CTL.